5PSQ-150 Traditional misuse of camphor powder: concerning two cases of paediatric poisoning. (March 2019) - Nchinech, N; Elgharbi, A; Aglili, FZ; Kriouile, Y; Cherrah, Y; Alaoui Mdaghri, AS; ,
Abstract : Background: In our country recourse to recipes of traditional medicine and homemade cosmetics is very frequent because of the high rate of illiteracy, low purchasing power and the large number of herbalists. Camphor is an inexpensive product, easily accessible and ubiquitous in almost all homes, making it a potential toxic for misuse, especially in children. Purpose: To present the story of two cases of intoxication consecutive to a beauty recipe based on camphor powder, in order to describe the importance of the sensitisation role exercised by the clinical pharmacist during the discharge interview. Material and methods: We analysed the files of the two patients during their hospitalisation in June 2018, and then we conducted face-to-face interviews with the mothers of the addicted children, and the attending physician. Results: The anamnesis gave information on a poisoning with a synthetic powder based on camphor imported from China in the two patients. Patient 1: Girl aged 2 months, without antecedents, admitted to the paediatric emergency department in a state of ceaseless crying with a refusal of food. The clinical examination was without any particular characteristics. The standard biological test was normal. The infant was under neurological, digestive and cutaneous supervision. Patient 2: Girl aged 6 years, admitted following atonic seizures with syncope and foam, followed by an installation of abdominal pain accompanied by food vomiting following ingestion of the milk. Evolution was favourable after 48 hours of symptomatic management. The interview with the mothers revealed that they were two neighbours who received a traditional recipe for the hair care of a third neighbour after which they mixed camphor powder with olive oil, then applied it to their children's hair for 1 hour, causing the appearance of these signs. As a result, a 30 min exit pharmaceutical interview was given to mothers to explain the dangers of using excessive traditional recipes. Conclusion: The interview with the mothers revealed that three other people used this preparation for their children, except that the duration of exposure was less than 30 min, which could justify the absence of harmful symptoms. It is advisable to integrate items on traditional recipes during pharmaceutical interviews with patients. References and/or acknowledgements: No conflict of interest.